Large-Scale Conformational Changes of FhaC Provide Insights Into the Two-Partner Secretion Mechanism - Sicoli, Giuseppe; Konijnenberg, Albert; Guérin, Jérémy; Hessmann, Steve; Del Nero, Elise; Hernandez-Alba, Oscar; Lecher, Sophie; Rouaut, Guillaume; Müggenburg, Linn; Vezin, Hervé; Cianférani, Sarah; Sobott, Frank; et al. (Frontiers in Molecular Biosciences, 2022)
The Two-Partner secretion pathway mediates protein transport across the outer membrane of Gram-negative bacteria. TpsB transporters belong to the Omp85 superfamily, whose members catalyze protein insertion into, or translocation across membranes without external energy sources. They are composed of a transmembrane β barrel preceded by two periplasmic POTRA domains that bind the incoming protein substrate. Here we used an integrative approach combining in vivo assays, mass spectrometry, nuclear magnetic resonance and electron paramagnetic resonance techniques suitable to detect minor states in heterogeneous populations, to explore transient conformers of the TpsB transporter FhaC. This revealed substantial, spontaneous conformational changes on a slow time scale, with parts of the POTRA2 domain approaching the lipid bilayer and the protein’s surface loops. Specifically, our data indicate that an amphipathic POTRA2 β hairpin can insert into the β barrel. We propose that these motions enlarge the channel and initiate substrate secretion. Our data propose a solution to the conundrum how TpsB transporters mediate protein secretion without the need for cofactors, by utilizing intrinsic protein dynamics.